2018
DOI: 10.1007/978-3-319-66766-9_4
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Waves in the Nonlinear Dirac Equation

Abstract: In the present work, we consider the existence, stability, and dynamics of solitary waves in the nonlinear Dirac equation. We start by introducing the Soler model of self-interacting spinors, and discuss its localized waveforms in one, two, and three spatial dimensions and the equations they satisfy. We present the associated explicit solutions in one dimension and numerically obtain their analogues in higher dimensions. The stability is subsequently discussed from a theoretical perspective and then complement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 170 publications
(305 reference statements)
1
15
0
Order By: Relevance
“…It was shown that there exist regions where gap solitons and defect modes are stable, and that the degree of nonlocality affects these regions drastically. The gap solitons have also been considered in the framework of PT-symmetric nonlinear Dirac model in [119].…”
Section: Generalized Nonlinear Potentialsmentioning
confidence: 99%
“…It was shown that there exist regions where gap solitons and defect modes are stable, and that the degree of nonlocality affects these regions drastically. The gap solitons have also been considered in the framework of PT-symmetric nonlinear Dirac model in [119].…”
Section: Generalized Nonlinear Potentialsmentioning
confidence: 99%
“…The half-soliton considered here is especially interesting as at the NLS level it turns out to be spectrally stable, yet nonlinearly unstable. This issue of the (more involved at the NLDE level [55]) spectral stability of these stationary states is also an especially interesting direction for future study.…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%
“…(2) The U(1) symmetry and the translation symmetry of the model result in zero eigenvalues with q = 0 and |q| = 1, respectively (in both S = 0 and S = 1 cases). (3) As in the 1d NLD equation, there are also the eigenvalues λ = ±2ωi which are associated with the SU(1, 1) symmetry of the model [47]. This eigenvalue pair corresponds to q = −(2S + 1), i.e., to a highly excited linearization eigenstate.…”
mentioning
confidence: 99%